Prompt and unavoidable requalification of ordinary hospital wards into a centralized department characterized by high-intensity treatment due to COVID-19 epidemic: the experience of Romano di Lombardia Hospital. Issue 1 (2nd January 2021) - Ceserani, Norberto; Motterlini, Enrico; Albergati, Michele; Barbieri, Fulvio; Valcarenghi, Marco; Carbone, Alessia; Bergonzi, Giovanni; Di Biase, Pasquale; Chiarello, Antonino; Colpani, Maria; Moretti, Francesca; Magnani, Anna; et al.
ABSTRACT: The Coronavirus epidemic quickly spread in Italy from China. In particular, it affected Bergamo province where Romano di Lombardia hospital is situated. Therefore, this hospital felt the urgency to requalify its activity in no time. It transformed itself into a unique centralized subintensive department to treat COVID-19 patients. The factors that made it possible to adequately face the stress due to patients' hospitalization were human resources and innovative elements to provide oxygen therapy. It is to underline that the logistic and methodological reality was not planned to cope with this emergency.